Lipidomic signature of the green macroalgae Ulva rigida farmed in a sustainable integrated multi-trophic aquaculture - Lopes, Diana (2019)
Ulva species, green macroalgae, are widely distributed across the globe, being one of the most heavily traded edible seaweeds. Nonetheless, although this genus has been largely used in scientific studies, its lipidome remains rather unexplored. The present study sheds light over the lipid profile of Ulva rigida produced in a land-based integrated multi-trophic aquaculture (IMTA) system using liquid chromatography coupled to high-resolution mass spectrometry for molecular lipid species identification. The lipidome of U. rigida revealed the presence of distinct beneficial n-3 fatty acids for human health, namely alpha-linoleic acid (ALA) and docosapentaenoic acid (DPA). A total of 87 molecular species of glycolipids, 58 molecular species of betaine lipids, and 57 molecular species of phospholipids were identified in the lipidome of U. rigida including some species bearing PUFA and with described bioactive properties. Overall, the present study contributes to the valorization and quality validation of sustainably farmed U. rigida.